2022
DOI: 10.1007/s11102-022-01263-7
|View full text |Cite
|
Sign up to set email alerts
|

Levoketoconazole in the treatment of patients with endogenous Cushing’s syndrome: a double-blind, placebo-controlled, randomized withdrawal study (LOGICS)

Abstract: Purpose The efficacy of levoketoconazole for endogenous Cushing’s syndrome was demonstrated in a phase 3, open-label study (SONICS). This study (LOGICS) evaluated drug-specificity of cortisol normalization. Methods LOGICS was a phase 3, placebo-controlled, randomized-withdrawal study with open-label titration-maintenance (14–19 weeks) followed by double-blind, randomized-withdrawal (~ 8 weeks), and restoration (~ 8 weeks) phases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…However, considering only the 55 patients who completed the maintenance phase, levoketoconazole induced a complete response in 61.8%, and induced a partial response in 16.4%, with an overall control in 78.2%, of patients, regardless of dose up-titration [ 8 ]. The phase III double-blind, placebo-controlled, randomized withdrawal study LOGICS has shown that levoketoconazole, at dosages of 300–1200 mg/day, induced a complete response in 50% of patients at the end of randomized withdrawal, percentage significantly higher if compared to placebo (4.5%) [ 9 ]. Moreover, at the end of randomized withdrawal, significantly more patients on placebo (95.5%) achieved the primary endpoint of loss of mean urinary free cortisol (mUFC) response, defined as mUFC > 1.5 upper limit of normal range, or, for SONICS completers with mUFC above the upper limit of normal range at baseline, an increase in mUFC > 40% above the baseline value, than those who continued on levoketoconazole (40.9%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, considering only the 55 patients who completed the maintenance phase, levoketoconazole induced a complete response in 61.8%, and induced a partial response in 16.4%, with an overall control in 78.2%, of patients, regardless of dose up-titration [ 8 ]. The phase III double-blind, placebo-controlled, randomized withdrawal study LOGICS has shown that levoketoconazole, at dosages of 300–1200 mg/day, induced a complete response in 50% of patients at the end of randomized withdrawal, percentage significantly higher if compared to placebo (4.5%) [ 9 ]. Moreover, at the end of randomized withdrawal, significantly more patients on placebo (95.5%) achieved the primary endpoint of loss of mean urinary free cortisol (mUFC) response, defined as mUFC > 1.5 upper limit of normal range, or, for SONICS completers with mUFC above the upper limit of normal range at baseline, an increase in mUFC > 40% above the baseline value, than those who continued on levoketoconazole (40.9%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phase III double-blind, placebo-controlled, randomized withdrawal study LOGICS has shown that levoketoconazole, at dosages of 300–1200 mg/day, induced a complete response in 50% of patients at the end of randomized withdrawal, percentage significantly higher if compared to placebo (4.5%) [ 9 ]. Moreover, at the end of randomized withdrawal, significantly more patients on placebo (95.5%) achieved the primary endpoint of loss of mean urinary free cortisol (mUFC) response, defined as mUFC > 1.5 upper limit of normal range, or, for SONICS completers with mUFC above the upper limit of normal range at baseline, an increase in mUFC > 40% above the baseline value, than those who continued on levoketoconazole (40.9%) [ 9 ]. The treatment with levoketoconazole was accompanied by an improvement in clinical syndrome and comorbidities of CS, including body weight, glucose metabolism, lipid profile, peripheral edema, quality of life and depressive status, as well as hirsutism and acne in women [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations